Damage Assessment of an SRC Frame-Core Tube Structure under the Action of a Main Aftershock Sequence - Peng Wang; Qingxuan Shi; Feng Wang; Siusiu Guo (Advances in Civil Engineering)
Historical seismic damage data show that most strong earthquakes are accompanied by multiple intense aftershocks. In general, the time interval between the main shock and the aftershocks is relatively short, and structure repair work is often not completed before the aftershocks occur. For a structure that has suffered damage from the main shock, the aftershock will further aggravate the damage and even cause complete collapse. Based on the incremental dynamic analysis (IDA) method, this paper establishes a probabilistic seismic demand model for the SRC framework-core tube structure and plots the vulnerability curve of a structure under the action of the main aftershock sequence, which occurs following the actions of frequent earthquakes, fortification earthquakes, and rare earthquakes. The structure vulnerability matrix and the vulnerability index are used to evaluate the seismic performance of a structure. This study found that the occurrence of aftershocks leads the structure to a more unfavourable failure state. Taking the vulnerability index as an evaluation parameter, the structural vulnerability index when subjected to an intensity 8 earthquake under the action of the main aftershock is approximately 10% larger than under the action of a single main shock. Meanwhile, the SRC frame-core structure designed according to the current Chinese specifications meets the expected seismic fortification target, even after being acted upon by the main aftershock ground motion sequence.